Organ-specific gene expression in transgenic potato: the cloning a new promoter of a class I patatin gene - Yefimenko, I.M.; Medvedeva, T.V.; Kovalenko, P.G.; Gazaryan, K.G.; Galkin, A.P. (Биополимеры и клетка, 1995)
Using synthetic oligonucleotide probes homologous to conservative AT-rich motif of patatin genes class I of two different clones were isolated from a potato genomic library. One of two different genomic clones named λpat122 was subcloned and analysis 5'-region sequences. Using the chloramphenicol acetyltransferase (CAT) gene as a reporter it has been shown that a 1.8 kb promoter fragment of the class I patatin gene λpat122 provides all the information necessary for both tuber-specific and sucrose-induced expression in leaves in transgenic potato plants.